Konwencjonalne zwroty wykrzyknikowe (quasi-religijne) ze składnikiem Bóg, Jezus, Matka Boska itp. w utworach Władysława Orkana - Kobylińska, Józefa (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2018)
The article is firmly rooted in the studies of religious language. The subject matter are secondary interjections incorporating words such as “Bóg”, “Jezus”, “Matka Boska”, gleaned from three W. Orkan’s novels: Komornicy [Landless Peasants], W roztokach [In the mountain dales] and Pomór [The Pestilence] as well as from his collected novellas and dramatic works. All exclamations may be divided into three groups: 1. those that function solely as interjections; 2. Those that function as both interjections and forms of address; 3. those that occur solely as forms of address. In addition to well-known linguistic units, the article analyses expressive phrases which are hitherto unmentioned in scholarly works and those which are only found in dialects.